Does Macroeconomic Policy Affect Private Savings in Europe? Evidence From a Dynamic Panel Data Model - Mechthild Schrooten; Sabine Stephan (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
Private savings mirror consumption behavior. In Europe, the dynamic of consumption is very low, and at the same time, savings are increasing. Is this a result of macroeconomic policy? A GMM estimator is used to analyze the determinants of private saving in the EU?s 15 member states. Our main findings are that savings rates inherit a certain degree of persistence and that income growth causes an increase in saving. While monetary policy is totally insignificant, fiscal policy has a major impact on private savings. The long-run effects of public deficits are greater than the effects of rising income.
Keywords: E21; C33; 330; Dynamic panel data model; private savings; European Union; GMM estimator; Sparen; Geldpolitik; Finanzpolitik; Wirtschaftspolitische Wirkungsanalyse; Schätzung; Einkommen; EU-Staaten